Existence and Nonexistence of Interfaces of Weak Solutions for Nonlinear Degenerate Parabolic Systems (Journal of Partial Differential Equations, 1996)
The existence and nonexistence of interfaces of weak solutions for nonlinear degenerate parabolic systems \frac{∂u_i}{∂t} - div (|∇u|^{p-2}∇u_i) = 0, i = 1, 2, …, m with p > 1 are studied in this paper.
Keywords: Nonlinear degenerate parabolic systems; weak solutions; imterfaces